Development of Competitive Environment in the Oil Market of Russian Federation: Empirical Analysis - Chernova, Elena Grigoryevna; Razmanova, Svetlana Valerievna (Economy of Regions, 2018)
The purpose of this research is the assessment of the competitive environment in the Russian oil market. The subject-matter of the study is the Russian oil and gas companies as a basis of the Energy market. We check the hypothesis about the development of the mechanism of corrective condition in the sphere of preliminary control of market concentrations in the fuel and energy complex (FEC). The basis of this research is the modern theory of industry markets studying various structures of the markets, the behavior of their participants, probable consequences of their functioning and interaction, as well as the impact of the state on the functioning of markets, its participants, and the results of their activities. We calculated and analyzed the key indicators characterizing the processes of market concentration in the oil industry. We also considered the competition policy of the Russian Federation in mergers and acquisitions deals (M&A deals) concerning oil and gas assets. The authors estimated over 460 decisions made by the Federal Antimonopoly Service of the Russian Federation for the period from 2011 to 2015 in the control on economic concentration in fu-el-and-energy industry. Based on the data characterizing the development of competitive environment, we have proved that the considered goods market belongs to markets with insufficiently developed competition. The results of the research will make a certain contribution to studying the efficiency of M&A transactions in the oil and gas industry, and also can be applied for the implementation of anti-monopoly actions by the Federal Antimonopoly Service of the Russian Federation.